Channels of Exit: Education-Led Vs. Labor-Led Out Migration Pathways among Youth in Nepal - Chuwan, Nar Kumar (BARUN Journal, 2026)
International migration has become a defining livelihood strategy and mobility pathway for Nepali youth. It is particularly structured into two distinct streams: an education-led departure to the Global North and a labor-led flow to the Gulf and Southeast Asia. This study compares these channels to examine how they operate as a stratified system that allocates youths according to pre-existing socioeconomic resources and shapes diverse life projects. Using a qualitative, comparative case study design, I conducted in-depth interviews with 24 Nepali youths (12 from each channel), recruited through educational consultancies and manpower agencies in Kathmandu. Guided by Pierre Bourdieu’s theory of capital, data were analyzed using thematic analysis (Braun & Clarke, 2006). Education-led migrants, typically having the luxury of higher economic and cultural capital, framed migration as an individual ‘self-project’ for long-term career advancement and global mobility. In contrast, labor-led migrants, driven by immediate economic pressures, approached migration as a familial ‘survival project’, often financing it through high-risk debt that mortgaged family assets. These different logics of aspiration and risk were reinforced by intermediaries, particularly educational consultancies and manpower agencies, which served as field-specific gatekeepers. The study concludes that these are not parallel pathways but a hierarchical system that globalizes domestic inequality. Rather than governing these flows separately, the study argues for an integrated policy lens that addresses the structural roots of this stratification.